(untitled) (Research, Society and Development, 2024)
Objective: To map the nursing focus in the existing literature on school-age children undergoing ENT surgery and their families, as well as their respective clinical data, nursing diagnoses, and nursing interventions. Methods: This scoping review will adhere to the Joanna Briggs Institute guidelines for Scoping Reviews and will consider published and unpublished evidence in English, Spanish and Portuguese. Databases including MEDLINE, CINAHL, PsycINFO, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, Scopus, JBI Evidence Synthesis and SciELO, along with sources of unpublished literature, such as ProQuest Dissertations and Theses and Repositório Científico de Acesso Aberto em Portugal, will also be searched for relevant studies. No cultural or geographical limitations will be applied. The study selection process will be reported using the PRISMA-ScR guidelines. Results: Two reviewers will independently extract the data using an extraction table. The first step is to identify the nursing focus, followed by presenting the remaining elements, specifically data, diagnoses and nursing interventions, organised in a figure that shows the relationships between them. Conclusion: By systematically presenting the current state of nursing knowledge in this field, this review will provide a foundation for enhancing clinical decision-making, improving the quality of nursing care delivered to school-age children undergoing ENT surgery and their families, and identifying areas for future research.